2018
DOI: 10.3389/fendo.2018.00185
|View full text |Cite
|
Sign up to set email alerts
|

Single-Gene Congenic Strain Reveals the Effect of Zbtb16 on Dexamethasone-Induced Insulin Resistance

Abstract: BackgroundGlucocorticoids (GCs) are potent therapeutic agents frequently used for treatment of number of conditions, including hematologic, inflammatory, and allergic diseases. Both their therapeutic and adverse effects display significant interindividual variation, partially attributable to genetic factors. We have previously isolated a seven-gene region of rat chromosome 8 sensitizing to dexamethasone (DEX)-induced dyslipidemia and insulin resistance (IR) of skeletal muscle. Using two newly derived congenic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 44 publications
0
9
0
Order By: Relevance
“…It is known that the induction or repression of GC targets above or below proper threshold can contribute to detrimental effects of GC excess in several tissues. For example, up-regulation of Zbtb16 and Txnip / Vdup has been reported in bone tissue in Cushing patients 36 , 37 . It is also worth noting the high overlap between the DEGs identified in this study and the gene expression changes in human skin of aged vs young subjects 10 .…”
Section: Discussionmentioning
confidence: 99%
“…It is known that the induction or repression of GC targets above or below proper threshold can contribute to detrimental effects of GC excess in several tissues. For example, up-regulation of Zbtb16 and Txnip / Vdup has been reported in bone tissue in Cushing patients 36 , 37 . It is also worth noting the high overlap between the DEGs identified in this study and the gene expression changes in human skin of aged vs young subjects 10 .…”
Section: Discussionmentioning
confidence: 99%
“…We used the spontaneously hypertensive rat (SHR/OlaIpcv, RGD ID 631848) because of its inherent abnormal metabolic profile [21] and its sensitivity manipulation by diet [22]. The SHR-Lx.PD5 PD-Zbtb16 single congenic strain (SHR-Zbtb16 hereafter) was derived from polydactylous rat (PD/Cub, RGD ID 728161) [23] and carries the Zbtb16 gene of PD origin on the SHR genomic background [24,25]. Both strains are highly inbred and maintained by brother x sister mating at the Institute of Biology and Medical Genetics.…”
Section: Methodsmentioning
confidence: 99%
“…At that time, SHR and SHR-Zbtb16 male offspring of both control (n = 8/strain) and experimental (n = 8/strain) groups were subjected to OGTT, blood draw for metabolic and lipid profile assessment and sacrificed to determine the weights of heart, liver, kidneys, adrenals, interscapular brown fat, epididymal and retroperitoneal fat pads. The lipid profile was assessed using high performance liquid chromatography (HPLC) for determining triglyceride (TG) and cholesterol (C) concentrations in 20 lipoprotein fractions and the size of major classes of lipoprotein particles as described previously [25,26]. F1 rat dams (n = 7/strain) were weighed regularly and subjected to OGTT at 16 weeks of age to determine the differences in glucose tolerance after being metabolically programmed by their maternal diet-either STD or HSD.…”
Section: Methodsmentioning
confidence: 99%
“…The SHR- Lx .PD5 PD– Zbtb16 single congenic strain (SHR- Zbtb16 hereafter) carries the Zbtb16 gene of polydactylous rat (PD/Cub, RGD ID 728161) origin on the SHR genomic background. The derivation of this strain was described previously ( Seda et al, 2005 ; Krupkova et al, 2018 ). Both strains are highly inbred and maintained by brother x sister mating at the Institute of Biology and Medical Genetics.…”
Section: Methodsmentioning
confidence: 99%
“…In addition to its role in adipogenesis, control of hepatic gluconeogenesis ( Chen et al, 2014 ), and cardiac hypertrophy ( Liska et al, 2017 ), genetic variation in human ZBTB16 was associated with increased obesity parameters and higher total and LDL cholesterol ( Bendlova et al, 2017 ). We have previously shown that rats carrying specific Zbtb16 allele are particularly sensitive to HSD, glucocorticoids, and retinoic acid in terms of induction of metabolic dysfunction ( Krupkova et al, 2014 , 2018 ). Therefore, we hypothesized that maternal HSD intake during pregnancy and lactation would program the offspring to develop metabolic alterations in adulthood and that these effects may be, to a certain extent, modified by genetic variation in Zbtb16 .…”
Section: Introductionmentioning
confidence: 99%